The Ordovician of southern South America - Waisfeld, Beatriz G.; Benedetto, Juan Luis; Toro, Blanca A.; Voldman, Gustavo G.; Rubinstein, Claudia V.; Heredia, Susana; Assine, Mario L. [UNESP]; Vaccari, N. Emilio; Niemeyer, Hans (Geological Society of London, 2023)
Early Paleozoic rocks are widespread, superbly exposed, and reach several thousand metres thick in southern South America. A largely quadripartite geotectonic subdivision of this huge area encompasses: (1) intracratonic basins forming the sedimentary cover of the Amazonian craton (Brazilian collage); (2) a clastic platform surrounding the Amazonian craton and the Pampia Terrane (Sierras Subandinas and Cordillera Orien-tal); (3) subduction-related parautochthonous volcanic arcs and associated volcano-sedimentary basins (Puna– Famatina arc); and (4) crustal fragments accreted to the proto-Andean margin of Gondwana (e.g. Cuyania Ter-rane). In this context, disparity in the geodynamic histories, preserved record and geological knowledge are remarkable. Biostratigraphical frameworks allow the recognition of global chronostratigraphical Ordovician subdivisions with fairly good resolution in the Early and Middle Ordovician of the Precordillera and the Early Ordovician of the Cordillera Oriental of Argentina. In Sierras Subandinas and Cordillera Oriental of Bolivia the Ordovician statigraphy is almost complete, although these extensive regions are still poorly known. In addition, trilobite-rich assemblages from the Cordillera Oriental and brachiopod-rich ones from Pre-cordillera and Famatina offer a remarkable template for dissecting regionally different scenarios underlying Ordovician diversifications. Overall, a more complete knowledge of this key area of Gondwana will certainly enhance our understanding of the global dynamics during the Ordovician.